2014
DOI: 10.1016/b978-0-12-800092-2.00010-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan–CD44 Interaction Promotes Oncogenic Signaling, microRNA Functions, Chemoresistance, and Radiation Resistance in Cancer Stem Cells Leading to Tumor Progression

Abstract: Hyaluronan (HA), a major component of the extracellular matrix (ECM), is enriched in many types of tumors. There is good evidence linking high levels of HA production in human carcinomas to an aggressive phenotype and tumor metastasis. HA is generally bound to CD44 isoforms (so-called CD44s and CD44v3) which are ubiquitous, abundant, and functionally important cell surface receptors. This chapter describes the evidence for HA/CD44v3-mediated activation of the cytoskeleton (e.g., ankyrin and GTPases) and matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 81 publications
(161 reference statements)
0
98
0
1
Order By: Relevance
“…The recent discovery of miRNAs in CSCs has broadened the area of gene regulation implicated in tumorigenesis and CSC modulation (35,42,43). In this study, we observed that HA is capable of stimulating DOT1L and H3K79 methylation in CSCs.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The recent discovery of miRNAs in CSCs has broadened the area of gene regulation implicated in tumorigenesis and CSC modulation (35,42,43). In this study, we observed that HA is capable of stimulating DOT1L and H3K79 methylation in CSCs.…”
Section: Discussionmentioning
confidence: 51%
“…Although certain anti-apoptotic proteins (e.g. Bcl-xL) have been shown to participate in anti-apoptosis and chemoresistance in HA/CD44-activated tumor cells, the involvement of IAPs in HA/CD44-mediated HNSCC cell survival and chemoresistance (10,13,42,43) has only recently started to receive attention. In this study we demonstrated that downregulation of HA/CD44-activated DOT1L signaling (by DOT1L siRNA) and miR-10b production (by anti-miR-10b inhibitor) inhibits the expression of survival proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, besides stimulating bone formation and reducing bone resorption, the alteration of GAG concentrations has also been reported to correlate with cancer progression by activating oncogenic pathways (92), promoting invasion and metastasis (93), and accelerating shedding of extracellular vesicles (94,95), which have to be carefully evaluated prior to clinical application. An alternative approach could be provided by dexamethasone, a synthetic glucocorticoid that was also shown to stimulate an osteoblast phenotype in vivo (96).…”
Section: Comparison Of the Matrix Vesicle Proteome With Hbmsc Proteomementioning
confidence: 99%
“…Hyaluronan is, however, highly dependent on the presence of CD44 in the cells, particularly in cancer stem cells, that survive immune attacks [52,53]. Interestingly, hyaluronan has also shown capacity to induce pro-inflammatory and pro-fibrotic cytokines [54], and to contribute to leukocyte recruitment from the blood circulation [55], indicating an interacting role in immunological systems [56].…”
mentioning
confidence: 99%